Synergetic Effects of Random Copolymerization/Backbone Fluorination and Heterojunction of Terpolymer/g‐C3N4 Enhance Photocatalytic Hydrogen Evolution. Issue 12 (3rd November 2022) - Jiao, Zhengxu; Wang, Jintao; Li, Zhanfeng; Tian, Yue; Liu, Baoyou; Yue, Gang
Abstract : In the field of photocatalytic hydrogen evolution, most polymer heterojunctions (PHJs) exhibit an unsatisfactory hydrogen evolution rate due to the decay of undissociated excitons, charge recombination, and weak light capture capacity. Herein, the design and synthesis of a series of D–A1 –D–A2 ‐type random conjugated terpolymers (DIn, n = 1, 2, 3) are reported by copolymerizing fluorinated 2, 2′‐bithiophene with different proportions of diketopyrrolopyrrole (DPP) and isoindigo (IID) for efficient vis‐light‐driven hydrogen evolution. Notably, the ternary copolymerization and fluorination strategy in the polymer backbone would enhance the intramolecular interactions and rebuild the extended π‐network over the polymeric heterojunction, which achieve broad and strong absorption ranging from 350 to 900 nm and a better effective photoexcitation separation, thus leading to a significantly increased hydrogen evolution reaction (HER) of 16.01 mmol h −1 g −1, via simply tuning the composition of DPP and IID units in the backbone of random terpolymers. The HER performance is almost 20 times higher than that of the typical g‐C3 N4 . This work offers a new strategy to develop efficient visible‐light‐driven photocatalysts via ternary copolymerization and backbone fluorination strategy of terpolymer/g‐C3 N4 PHJs for broadband solar photon harvesting. Abstract : A series of 1D/2A random terpolymers for visible light‐driven H2 evolution is presented. The g‐C3 N4 /terpolymer heterostructures boost the photocatalytic activity. The synergetic effects of the ternary copolymerization and fluorination strategy promote solar photon harvesting.